Distribution of different types of expressive lexicon in 18-24-monthold Sorani-Kurdish-speaking children - Serve Zarehi; Talieh Zarifian; Hosaine Rahmani; Samaneh Hoseinzadeh (Shiraz University of Medical Sciences, 2016)
Background: In the age of 18-19 months, a child's lexicon increases by acquisition of five words per week. Linguists consider this a period of vocabulary spurt. In the early stages of language acquisition, the diversity of vocabulary also increases in addition to an increase in the number of words. The goal of the present study was to examine the distribution of different types of expressive words in 18-24-month-old Sorani-Kurdish-speaking children. Methods: The present research was conducted in a longitudinal form (for three months) on 16 Kurdish infants of Bukan 81 fo syob ruof dna slrig ruof) syob ruof dna slrig ruof dna ,ega ni shtnom of 21 months). Normal children were selected, based on their health and demographic records. The data collection materials included a weekly vocabulary recording sheet, a vocabulary list, and a demographic questionnaire. All the data were analyzed using SPSS version 22 software, with the significance level set at 0. 05. Since the data were normally distributed, ot detcejbus erew selpmas tnednepedni T-tests and repeated measures ANOVA were used to compare the vocabulary distribution (nouns, adjectives, verbs, and adverbs) in gender and age groups. Results: There was no significant difference between genders in the number and type of words (P>0.05). In both groups, with increasing age, the number and variation of the words increased (P<0.05). The most frequently expressed words were nouns, adjectives, verbs and adverbs. Among the expressed nouns, the most common ones were food categories (19.51%). Of the expressed adjectives, the most common ones related to condition. Among the expressed verbs, the most common ones were imperatives (80%) and positives (90%). Among the expressed adverbs, the most common ones were adverbs of place (90%). Conclusion: It seems from the findings that the distribution and diversity of vocabulary categories follow a pattern similar to other languages.